2021
DOI: 10.1371/journal.pone.0257693
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impacts of COVID-19 among LGBTQ2S youth experiencing homelessness

Abstract: Background LGBTQ2S youth are overrepresented among youth experiencing homelessness and experience significantly higher rates of mental health issues compared to heterosexual and cisgender youth. COVID-19 related challenges for LGBTQ2S youth experiencing homelessness remain unknown. To address this gap, this study aimed to understand the impacts of the COVID-19 pandemic on LGBTQ2S youth at risk of, and experiencing, homelessness in the Greater Toronto Area, Ontario, Canada and surrounding areas. Methods Utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“… 24 Although we have not shown an increase in institutionalized adolescents or those at risk of social exclusion, some authors have pointed out the special vulnerability of specific groups. 25 …”
Section: Discussionmentioning
confidence: 99%
“… 24 Although we have not shown an increase in institutionalized adolescents or those at risk of social exclusion, some authors have pointed out the special vulnerability of specific groups. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Staff also expressed concerns about youth that identify as 2SLGBTQ+ as they were faced with reduced access to affirming communities and social supports and thus experienced increased feelings of isolation. Service providers must be particularly vigilant in providing outreach and support to youth that identify as 2SLGBTQ+ as research has shown that 2SLGBTQ+ young people are more likely to experience mental health distress, including depression suicidal ideation [ 41 , 42 ] and that these concerns have become particularly acute during the pandemic [ 22 , 43 ]. For instance, Abramovich et al [ 22 ] found that in their sample of 92 2SLGBTQ+ youth in the Greater Toronto Area, the vast majority reported experiencing severe anxiety, moderate to severe depression, and increased loneliness as a result of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Research on transgender and gender-diverse youth during the pandemic found higher rates of adverse mental health compared to young people who are cisgender, as well as greater difficulty accessing services and family supports [ 14 ]. Looking at the experiences of 2SLGBTQ+ youth more broadly in a mixed-methods study with 61 youth that identified as 2SLGBTQ+, the majority of whom were precariously housed or homeless, the authors reported high rates of poor mental health, presence of non-suicidal self-harm behaviours, increased substance use and suicidal ideation related to the pandemic [ 22 ]. An alarming thirty-six percent of study participants reported attempting suicide since the start of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…533–543), [ 8 ] (pp. 773–782); polytrauma and abuse [ 9 ] (p. 16), [ 10 ] (p. 216), [ 11 ] (pp. 894–910), [ 12 ] (pp.…”
Section: Introductionmentioning
confidence: 99%